Reaching out to Africa’s Orphans A Framework for Public Action - World Bank (World Bank, Washington, DC, 2012)
Conflicts and the HIV-AIDS pandemic are generating a major humanitarian crisis in Sub-Saharan Africa: the number of children who have lost one or both parents is expected to rise to 35 million by 2010. Even prior to the death of parents, children are vulnerable as prolonged sickness of a parent robs them of their childhood, often forcing them to become breadwinners. The risk of orphanhood is no longer a random shock affecting a few families; it is a systemic shock affecting whole communities and large segments of the population.